Effect of Ta Content on the Microstructure and Mechanical Properties of Laser Additive Manufactured Nickel-Based Superalloys - GUO Liangliang, WU Wenxing, YANG Tong, CHEN Pinghu, JIN Xuming, ZHU Tao, ZOU Xinchang, QIU Changjun (Cailiao Baohu)
Alloys with low Ti/Al content exhibit insufficient strength，while those with high Ti/Al content are prone to cracking during laser additive manufacturing.To achieve a balance between high γ′ phase volume fraction and low crack susceptibility，this study proposed an alloy design strategy: appropriately reducing Ti/Al content while increasing Ta content based on the high-Ti/Al IN738LC alloy.Based on this design strategy，the microstructures and properties of four laser additive as-deposited samples with different Ta contents before and after solid solution treatment and aging treatment were studied.Results showed that with increasing Ta content，the as-deposited samples exhibited grain refinement and a higher γ′ phase fraction.The tensile strength and yield strength of both as-deposited and heat-treated samples increased as the Ta content increased，while their ductility decreased and cracking susceptibility intensified.When the mass fraction of Ta in the heat-treated samples reached 5%，η-phase precipitation occurred.At 7%Ta content，excessive η-phase formation led to brittle fracture surfaces in tensile specimens.Moreover，the sample with 5%Ta exhibited an optimal strength-ductility combination: at 25 ℃，yield strength of 962 MPa，ultimate tensile strength of 1 212 MPa，and elongation of 11.0%；while at 900 ℃，yield strength of 410 MPa，ultimate tensile strength of 486 MPa，and elongation of 6.1%.Generally，through optimization of Al，Ti and Ta contents，this study successfully developed a γ′-phase strengthened laser additive manufactured nickel-based superalloy.The alloy achieved an optimal balance between high γ′-phase volume fraction and low cracking susceptibility，demonstrating excellent comprehensive mechanical properties，and these findings provided valuable insights for the compositional design of laser additive manufactured nickel-based superalloys.